2023
DOI: 10.1111/dom.15185
|View full text |Cite
|
Sign up to set email alerts
|

All‐cause mortality and cardiovascular outcomes with sodium‐glucose Co‐transporter 2 inhibitors, glucagon‐like peptide‐1 receptor agonists and with combination therapy in people with type 2 diabetes

David R. Riley,
Hani Essa,
Philip Austin
et al.

Abstract: AimTo assess the relationship of sodium‐glucose cotransporter‐2 inhibitors (SGLT2i), glucagon‐like peptide‐1 receptor analogues (GLP‐1RA) and their combination (SGLT2i + GLP‐1RA) with 5‐year risk of all‐cause mortality, hospitalization and cardiovascular/macrovascular disease in people with type 2 diabetes.Materials and MethodsRetrospective cohort analysis of 2.2 million people with type 2 diabetes receiving insulin across 85 health care organizations using a global federated health research network. Three int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…2 . Quantitative meta-analysis was performed using 8 studies [ 23 , 26 31 , 33 ]. The remaining 5 studies were considered to be ineligible for inclusion in this meta-analysis as mean values were not available (n = 1), follow-up duration was less than 6 months (n = 2), and only differences in outcomes were provided instead of absolute values (n = 2) (Additional file 1 : Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…2 . Quantitative meta-analysis was performed using 8 studies [ 23 , 26 31 , 33 ]. The remaining 5 studies were considered to be ineligible for inclusion in this meta-analysis as mean values were not available (n = 1), follow-up duration was less than 6 months (n = 2), and only differences in outcomes were provided instead of absolute values (n = 2) (Additional file 1 : Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, our study demonstrated benefit in a cohort without preexisting cardiorenal disease. Our previous real-world data study has demonstrated that combination therapy with SGLT2i and GLP-1 RA conferred mortality and cardiovascular protection in T2D over 5 years, particularly in all-cause mortality [ 21 ]. Current joint ADA (American Diabetes Association) and EASD (European Association for the Study of Diabetes) guidelines [ 9 ] suggest initiating GLP-1 RA or SGLT2i instead of metformin as first-line therapy only in individuals with high ASCVD risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…A meta‐analysis has suggested that, compared with single drug treatment, the combination of two classes of drugs confers more benefits regarding blood glucose, blood pressure, and blood lipid 104 . A retrospective cohort study has found that, compared with single drug treatment, combined therapy with SGLT2 inhibitors and GLP‐1RAs achieves better all‐cause mortality and cardiovascular benefits 105 . However, little high‐quality evidence to date has demonstrated the clinical benefits of combined therapy with these two drugs in the older population.…”
Section: Chapter 8: Glycemic Medications and Treatment Strategies For...mentioning
confidence: 99%
“… 104 A retrospective cohort study has found that, compared with single drug treatment, combined therapy with SGLT2 inhibitors and GLP‐1RAs achieves better all‐cause mortality and cardiovascular benefits. 105 However, little high‐quality evidence to date has demonstrated the clinical benefits of combined therapy with these two drugs in the older population.…”
Section: Chapter 8: Glycemic Medications and Treatment Strategies For...mentioning
confidence: 99%